Influence of engine operating variable on combustion to reduce exhaust emissions using various biodiesels blend - Wakil, M.A.; Masjuki, Haji Hassan; Kalam, M.A.; Teoh, Y.H.; How, H.G.; Imtenan, S. (Royal Society of Chemistry, 2015)
This study focused mainly on the behavior of biodiesel operated under various operating conditions. The experiment was conducted with B20 of three potential biodiesel sources, namely, rice bran, Moringa and sesame oil. A significant outcome was observed from the test results, which showed that the brake thermal efficiency of the biodiesel blend was about 3.4% lower under constant speed running conditions than constant torque operating conditions. Similarly, about 6.5% lower exhaust gas temperatures under constant speed running conditions with lower peak pressure were found than under constant torque testing conditions. On the subject of emission, it is seen that the testing conditions also have an influence on exhaust emission. For instance, under constant speed running conditions, the engine produces about 19.5% lower NO and 19% higher HC than under constant torque running conditions. A similar influence was also found in the pressure and heat release rate. However, there is a clear variation found in the results under different operating conditions. Therefore, it is necessary to test the fuel under various operating conditions, such as constant torque, constant speed, variable injection timing, for the optimal use of biodiesel.